2014
DOI: 10.1155/2014/573470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbal Essential Oil Mixture as a Dietary Supplement on Egg Production in Quail

Abstract: One hundred and eighty 7-week-old laying quail were fed various diets over a 12-week period. The diets included a control diet (without essential oil mixture (EOM) or antibiotics (ANTs)), a basal diet including EOM (24 mg/kg feed), and a basal diet including an ANT (avilamycin, 10 mg/kg feed). Each treatment comprised 4 replications with 4 cages (15 quail per cage), amounting to 60 quail per treatment group. Diets (in mash form) and water were provided for ad libitum consumption. EOM consisted of 6 different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
3
15
1
1
Order By: Relevance
“…In order to find effective substitutes to antibiotic growth promoters, several aromatic plants have been evaluated in poultry industry (Abudabos, Alyemni, Dafallah, & Khan, ; Khan, Naz, Nikousefat, Tufarelli, & Laudadio, ). These herbs, or their extract, show significant antimicrobial, antifungal, antioxidant, and physiological modulation proprieties (Ardalan, Omid, Golnaz, & Mahdi, ; Çabuk, Eratak, Alçicek, & Bozkurt, ; Jang, Ko, Kang, & Lee, ). Moreover, natural extracts also can serve as natural antioxidant limiting lipid oxidation in meat and meat products (Dhama et al., ; Shah, Bosco, & Mir, ; Tufarelli, Laudadio, & Casalino, ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to find effective substitutes to antibiotic growth promoters, several aromatic plants have been evaluated in poultry industry (Abudabos, Alyemni, Dafallah, & Khan, ; Khan, Naz, Nikousefat, Tufarelli, & Laudadio, ). These herbs, or their extract, show significant antimicrobial, antifungal, antioxidant, and physiological modulation proprieties (Ardalan, Omid, Golnaz, & Mahdi, ; Çabuk, Eratak, Alçicek, & Bozkurt, ; Jang, Ko, Kang, & Lee, ). Moreover, natural extracts also can serve as natural antioxidant limiting lipid oxidation in meat and meat products (Dhama et al., ; Shah, Bosco, & Mir, ; Tufarelli, Laudadio, & Casalino, ).…”
Section: Introductionmentioning
confidence: 99%
“…For several years, the dietary use of antibiotics has been extensively used throughout the world as growth promoters in animal feeds, particularly in poultry products [1] . However, many countries have banned the use of antibiotics in animal feed as an additive since their use may lead to the antibiotic resistant bacteria which are harmful to humans [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with our observation, it has been previously demonstrated that a diet containing an essential oil mixture (EOM) at 24 mg/kg diet improved egg production and feed efficiency and decreased the percentage of broken eggs in laying hens (Çabuk, Bozkurt, Alçiçek, Çatlı et al., ). Additionally, a study on laying quails also showed increased egg production and FCR by dietary EOM (Cabuk, Eratak, Alcicek, & Bozkurt, ). The improved egg production by dietary phytoncides seems to be related to its unique physiological properties on the function of the gastrointestinal (GI) tract.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a study on laying quails also showed increased egg production and FCR by dietary EOM (Cabuk, Eratak, Alcicek, & Bozkurt, 2014). The improved egg production by dietary phytoncides seems to be related to its unique physiological properties on the function of the gastrointestinal (GI) tract.…”
Section: Discussionmentioning
confidence: 99%